Building serverless applications - Villalba, Marcia; Safari eBooks ([Place of publication not identified] : Packt, 2018)
"Serverless applications have been transforming web development for the last few years. They help you manage the complexity of today's applications and tackle the demands of today's users in a way, unlike any other previous serverless framework. This course will take you through serverless applications using AWS Lambda. In this course, you'll build a Slack bot to manage tasks. Slack users will be able to send tasks to the bot, get all pending tasks in the Slack channel from the bot, and complete individual tasks; when a task gets close to the due date the service will send a reminder to Slack. The course will teach you to write your first serverless application with events and triggers. Moving ahead, you will learn to deploy your application to the cloud and study the tools used in creating applications. Use this course to finally get to grips with a serverless application, and become a more confident and smarter developer. The course will help you understand what serverless applications are and how you can use them to build a production-ready application."--Resource description page.
Presenter, Marcia Villalba.
Title from title screen (viewed February 7, 2018).
Date of publication from resource description page.
Keywords: Amazon Web Services (Firm); Web applications -- Development; Application software -- Development; Cloud computing; Electronic books